Onstage violence in sixteenth-century French tragedy - Meere, Michael (Oxford University Press, 2021)
This volume studies the representation of violence in tragedies written for the French stage during the sixteenth century, and explores its connection with issues such as politics, religion, gender, and militantism to place the plays within their historical, cultural, and theatrical contexts.
10.1093/oso/9780192844132.001.0001
Keywords: Violence in literature; Violence in the theater; French drama